2013
DOI: 10.1016/j.ympev.2013.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of the Notostraca

Abstract: a b s t r a c tWe used a combined analysis of one nuclear (28S rDNA) and three mitochondrial markers (COI, 12S rDNA, 16S rDNA) to infer the molecular phylogeny of the Notostraca, represented by samples from the six continents that are inhabited by this group of branchiopod crustaceans. Our results confirm the monophyly of both extant notostracan genera Triops and Lepidurus with good support in model based and maximum parsimony analyses. We used branchiopod fossils as a calibration to infer divergence times amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 61 publications
6
23
0
1
Order By: Relevance
“…further emphasized the noteworthy cryptic diversity lumped under this binomen. Korn et al (2013) even demonstrated that T. granarius is paraphyletic with respect to the remaining congeneric species, thus further highlighting the need for a revision of the taxon. Other references: Seurat (1922), Longhurst (1955), Turki and Turki (2010).…”
Section: Triops Granarius (Lucas 1864)mentioning
confidence: 96%
See 3 more Smart Citations
“…further emphasized the noteworthy cryptic diversity lumped under this binomen. Korn et al (2013) even demonstrated that T. granarius is paraphyletic with respect to the remaining congeneric species, thus further highlighting the need for a revision of the taxon. Other references: Seurat (1922), Longhurst (1955), Turki and Turki (2010).…”
Section: Triops Granarius (Lucas 1864)mentioning
confidence: 96%
“…Mantovani et al 2009, Korn et al 2013, further evidence is needed in order to clarify which of the populations presently attributed to this subspecies might actually refer to the former L. lubbocki described by Brauer (1873). The situation is complicated by the fact that L. a. lubbocki turned out to be paraphyletic with respect to the remaining species in the genus hitherto studied via molecular tools (see Figs. 1 and 2 in Korn et al 2013). Furthermore, no specimens from the type locality have ever been investigated using modern methods, so that a possible taxonomical re-instatement should await a profound re-investigation of Circum-Mediterranean populations.…”
Section: Lepidurus Apus Lubbocki Brauer 1873mentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, dispersal often occurs through multiple processes and vectors (Higgins et al, 2003). In this review, we will put a special focus on temporary water bodies, since these ecosystems represent biodiversity hotspots (Williams et al, 2001;Zacharias et al, 2007) and their functioning and conservation strictly depends on the dispersal and colonization abilities of their biota (Sahuquillo & Miracle, 2013;Marrone et al, 2013;Korn et al, 2013). Moreover, temporary ponds, alternating flooded and dry phases, add the duration of their ponding phase as a further temporal dimension to their ''insular features'' (Ebert & Balko, 1987;NaselliFlores & Barone, 2012).…”
Section: Introductionmentioning
confidence: 99%